Antifibrotic Effects of a Barbituric Acid Derivative on Liver Fibrosis by Blocking the NF-κB Signaling Pathway in Hepatic Stellate Cells - Wang, Yuan-Hsi; Suk, Fat-Moon; Liu, Chao-Lien; Chen, Tzu-Lang; Twu, Yuh-Ching; Hsu, Ming-Hua; Liao, Yi-Jen (Frontiers in Pharmacology, 2020)
Hepatic stellate cells (HSCs) are the major profibrogenic cells that promote the pathogenesis of liver fibrosis. The crosstalk between transforming growth factor-β1 (TGF-β1) signaling and lipopolysaccharide (LPS)-induced NF-κB signaling plays a critical role in accelerating liver fibrogenesis. Until now, there have been no FDA-approved drug treatments for liver fibrosis. Barbituric acid derivatives have been used as antiasthmatic drugs in the clinic; however, the effect of barbituric acid derivatives in treating liver fibrosis remains unknown. In this study, we synthesized a series of six barbituric acid (BA) derivatives, and one of the compounds, BA-5, exhibited the best ability to ameliorate TGF-β1-induced HSC activation without overt cytotoxic effects. Then, we treated HSCs and RAW264.7 macrophages with BA-5 to analyze the cross-talk of anti-fibrotic and anti-inflammatory effects. Carbon tetrachloride (CCl4)-induced liver fibrosis mouse model was used to evaluate the therapeutic effects of BA-5. Treatment with BA-5 inhibited TGF-β1-induced α-SMA, collagen1a2, and phosphorylated smad2/3 expression in HSCs. Furthermore, BA-5 treatment reversed the LPS-induced reduction in BAMBI protein and decreased IκBα and NF-κB phosphorylation in HSCs. NF-κB nuclear translocation, MCP-1 secretion, and ICAM-1 expression were also inhibited in BA-5-treated HSCs. Conditioned medium collected from BA-5-treated HSCs showed a reduced ability to activate RAW264.7 macrophages by inhibiting the MAPK pathway. In the mouse model, BA-5 administration reduced CCl4-induced liver damage, liver fibrosis, and F4/80 expression without any adverse effects. In conclusion, our study showed that the barbituric acid derivative BA-5 inhibits HSCs activation and liver fibrosis by blocking both the TGF-β1 and LPS-induced NF-κB signaling pathways and further inhibits macrophages recruitment and activation.